MANAJEMEN MUTU PENDIDIKAN BERBASIS PESANTREN (Studi Kasus MA Al Mawaddah Warrahmah Kolaka) - Nur Faidah Samad (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
One of the most important issues in the implementation of education in Indonesia is the increase in quality, especially the improvement of the quality of Islamic boarding school-based education. Islamic boarding school based education is an education that upholds the values ​​and traditions of the Islamic boarding school. MA Al Mawaddah Warrahmah Kolaka at the beginning of its establishment was not very well known among the people, it was proven that the first graduates of the Kolaka MA Al Mawaddah Warrahmah only amounted to 11 people. But with enthusiasm slowly changing and experiencing a shift from traditional management to more modern management that is quality oriented. This research aims to reveal the quality management of MA Al Mawaddah Warrahmah Kolaka with sub focus which includes: 1) quality management planning, 2) implementation of quality management, 3) implications of quality management. This study uses a descriptive qualitative approach. The results of the study show that: (1) The planning of boarding-based education quality conducted at Kolaka MA Al Mawaddah Warrahmah through the following stages: a) Islamic Boarrding School-based education quality planning preparation begin with data collection, then data was analyzed, then formulates the quality to be achieved . b) Islamic Boarding School based education quality planning based on eight national education standards (SNP). (2) Implementation of boarding-based education quality management at MA Al Mawaddah Warrahmah Kolaka was carried out with four superior programs including daily programs (duha prayer together and checking students by each homeroom), weekly programs (extracurricular activities), monthly programs (workshops, MGMP , attendance control, and semester programs (Porseni and Arabic and English Villages) (3) The implication of the quality management of boarding-based education at MA Al Mawaddah Warrahmah was increasing education output and outcome, forming consensus on improving quality, providing advice and infrastructure faster, increasing discipline, enthusiasm for innovation and improvisation, increasing public trust, and teacher loyalty was getting higher